Development and Laboratory Validation of Rapid, Bird-Side Molecular Diagnostic Assays for Avian Influenza Virus Including Panzootic H5Nx - Matthew Coopersmith; Remco Dijkman; Maggie L. Bartlett; Richard Currie; Sander Schuurman; Sjaak de Wit (Microorganisms)
Avian influenza A viruses (AIV) significantly impact both animal and human health. Reliable diagnostics are crucial for controlling AIV, including the highly pathogenic strains like H5Nx. In this study, we developed and validated the on-site Alveo Sense Poultry Avian Influenza Tests to rapidly detect the AIV M-gene and subtypes H5, H7, and H9 in unprocessed samples using reverse-transcription loop-mediated isothermal amplification (RT-LAMP) and impedance-based measurements. The Alveo Sense tests, using single-use microfluidic cartridges, deliver results within 45 min. Each cartridge includes assays for the AIV M gene and specific H5 and H7 or H9 subtypes, with internal process controls. The laboratory validation involved specificity, limit of detection (LoD), diagnostic sensitivity, reproducibility, and robustness tests using various AIV strains, other avian pathogens, and field samples. The assays showed 100% specificity for AIV subtypes without cross-reactivity with non-AIV pathogens. The LoD95 for H5, H7, and H9 ranged between RT-PCR Ct values of 29–33 in both cloacal and oropharyngeal samples and were able to detect avian influenza virus in both spiked samples and field samples. Reproducibility and repeatability studies showed perfect agreement across operators and laboratories and remained stable and accurate under different pre-analytical conditions. The Alveo Sense tests offer rapid, accurate, and reliable on-site diagnostics for AIV subtypes H5, H7, and H9 on samples from fresh dead and sick birds, valuable for early flock-level detection and outbreak control. Further field validation will improve the understanding of their diagnostic performance across various avian species.